CRNDE: A Long Non-Coding RNA Involved in CanceR, Neurobiology, and DEvelopment - Ellis, Blake C.; Molloy, Peter L.; Graham, Lloyd D. (Frontiers in Genetics, 2012)
CRNDE is the gene symbol for Colorectal Neoplasia Differentially Expressed (non protein-coding), a long non-coding RNA (lncRNA) gene that expresses multiple splice variants and displays a very tissue-specific pattern of expression. CRNDE was initially identified as a lncRNA whose expression is highly elevated in colorectal cancer, but it is also upregulated in many other solid tumors and in leukemias. Indeed, CRNDE is the most upregulated lncRNA in gliomas and here, as in other cancers, it is associated with a “stemness” signature. CRNDE is expressed in specific regions within the human and mouse brain; the mouse ortholog is high in induced pluripotent stem cells and increases further during neuronal differentiation. We suggest that CRNDE is a multifunctional lncRNA whose different splice forms provide specific functional scaffolds for regulatory complexes, such as the polycomb repressive complex 2 (PRC2) and CoREST chromatin-modifying complexes, which CRNDE helps pilot to target genes.